2019
DOI: 10.1016/j.immuni.2019.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Permeability and IgA Provoke Immune Vasculitis Linked to Cardiovascular Inflammation

Abstract: Highlights d IL-1b-driven increased intestinal permeability is observed in murine KD model d Blocking intestinal permeability or IgA production decreases murine KD vasculitis d IgA and IgA-C3 are observed in cardiovascular lesions of murine KD model d KD vasculitis may be a form of IgA vasculitis involving a gutvascular axis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 67 publications
3
76
0
Order By: Relevance
“…IL-1β is a key mediator in sepsis-induced inflammation and tissue injury (10,11,29). Macrophage-generated IL-1β acting through IL-1R1 during sepsis disrupted vascular stability (11,26).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a key mediator in sepsis-induced inflammation and tissue injury (10,11,29). Macrophage-generated IL-1β acting through IL-1R1 during sepsis disrupted vascular stability (11,26).…”
Section: Discussionmentioning
confidence: 99%
“…include cardiovascular and lung disorders, diabetes, and cancer. 65 Many of the specific medical conditions that are included within these groups of disorders are linked to an elevation in gut dysbiosis/ permeability, 66,67 mitochondrial dysfunction, 68 and circadian dysregulation, 69,70 with melatonin showing utility in their management. 71,72 Ageing, the main risk factor for death from influenza and covid-19, is highly associated with these pathophysiological changes, [73][74][75][76] with melatonin, partly via sirtuin induction as well as circadian and mitochondria regulation, attenuating ageing-associated processes.…”
Section: Preexisting Medical Conditionsmentioning
confidence: 99%
“…These results might support the hypothesis of the Kawasaki disease that occurred coincidentally during HSP. In contrast, Noval Rivas et al [22] showed that strong evidence that intestinal IgA production is increased during the acute phase of Kawasaki disease in human patients and in a murine model of Kawasaki disease vasculitis. Moreover, they showed that intestinal epithelial barrier dysfunction in this model results in sIgA leakage and sIgA-C3 complex deposition in to vascular tissues and glomeruli.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, they showed that intestinal epithelial barrier dysfunction in this model results in sIgA leakage and sIgA-C3 complex deposition in to vascular tissues and glomeruli. They concluded that these data suggest that Kawasaki disease may be a form of IgA vasculitis [22].…”
Section: Discussionmentioning
confidence: 99%